Current Issues in Corporate Social Responsibility An International Consideration (CSR, Sustainability, Ethics & Governance,, 2018)
This book takes a fresh look at current issues in corporate social responsibility (CSR) with a special focus on emerging economies. In particular, it includes dedicated chapters on the theory of CSR, related principles and values, and insights from cross-generational investigations. In turn, the second part of the book examines the relation between financial performance and social responsibility in different industries and types of organizations. The third part presents cases involving emerging economies, and addresses reporting, auditing and accounting, as well as sector-specific issues for e.g. retailing and banking. Lastly, the book tackles the aspects of financial performance and taxation in a number of case studies and practical examples. Overall the book provides cutting-edge insights into the theory and practice of CSR from European countries that can be considered emerging or developing.